What drives nickel prices: A structural VAR approach - Lars G. Ehrlich (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2018)
Metal markets play a major role in the challenging area of natural resource economics and have a forceful impact on global and local development. Understanding the behaviour and nature of metal price fluctuation is an essential element for taking countermeasures. Nickel is an indispensable element for modern steel industries and therefore crucial to industrial countries. This paper presents a structural model to explain price fluctuations in the international nickel market. On the basis of a unique long-term data set from 1867 to 2015, demand and supply shocks affecting the real prices of nickel are identified by using a Structural Vector Autoregression (SVAR) model and are traced back to historical developments in the nickel market. The results demonstrate that in the late 19th century real nickel prices were most affected by 'nickel-specific' demand shocks as well as "nickel supply" shocks. While over the course of the 20th century the weight of positive "world domestic product driven" demand shocks grew, from 1980 on nickel-specific demand shocks had the most influence on nickel price development. These findings underline the need to analyse the driving forces of metal prices individually and thereby take its particular features into account rather than generalising over a broad spectrum of mineral commodities.
Keywords: 330